Review of the genus Apolysis Loew, 1860 (Diptera: Bombyliidae: Apolysini) from Iran, with taxonomic notes on the pusilla species group - Gharali, Babak; Evenhuis, Neal; Dils, Jozef (Zootaxa, 2026)
Apolysis Loew is a speciose genus of bee flies (Bombyliidae) distributed throughout the Northern Hemisphere. The genus is reviewed in Iran based on the examination of type material of previously recorded species. The species Apolysis flavipes (Efflatoun, 1945) belonging to the pusilla species group, is redescribed and recorded from Iran for the first time. Apolysis szappanosi Papp, 2005, syn. nov. is found to be the conspecific with Apolysis pusilla (Paramonov), and also redescribed here. An identification key to the species of Apolysis known from Iran is provided, and the status of the genus Dagestania Paramonov is briefly discussed.